Tinjauan Kritis: Kompleksitas Sosial Caregiver Demensia dalam Keluarga Usia Lanjut - Kreshna Manggala Putra; Ida Ruwaida Noor (Jurnal Syntax Transformation, 2021)
This article aims to provide a critical review of the study of Struckmeyer and Roberts which focuses on examining the family dynamics of 2 (two) cases in the lives of 2 family couples who take the role of caregiver to care for People with Dementia in their household. Methods using qualitative literature study was conducted to see the strengths and limitations of this issue. His strength is to be able to explore the dynamics of the caregiver life of People with Dementia, especially related to the depiction of the dynamics of the interaction between husband and wife in families who experience the caregiving process in old age. Struckmeyer is able to address issues that is rarely get attention in other studies of dementia problems in general, namely, the special problems experienced by the caregiver itself. Meanwhile, Struckmeyer is limited in exploring the subjects family's social background and social environment. The conclusion of this article places Struckmeyer in less demonstrating the social characteristics of the family and the local environment due to help readers understand other supportive situations that shape the meaning of informants in living their lives as dementia caregivers.